2020
DOI: 10.1002/acm2.12808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiation dose and image quality between flat panel computed tomography and multidetector computed tomography in a hybrid CT‐angiography suite

Abstract: The purpose of this study was to compare, using the same radiation dose and image quality metrics, flat panel computed tomography (FPCT) to multidetector CT (MDCT) in interventional radiology. A single robotic angiography system with FPCT was compared to a single MDCT system, both installed in a hybrid CT‐angiography laboratory and both operating under automatic exposure control. Radiation dose was measured on the central axis (Dc) of a CT dosimetry phantom 30 cm in diameter and 60 cm in length using default p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In contrast, both FD-CT systems had higher CTDI vol and DLP compared to MS-CT—regardless of the applied scanning protocol. This is in accordance to previous studies reporting effective doses for angiography-mounted FD-CT systems up to twice as high as for MS-CT [ 19 , 23 , 24 ]. In our study, the 14-s scanning protocol of the HS-FD-CT presented with the highest CTDI vol and DLP among the tested scanners and protocols.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, both FD-CT systems had higher CTDI vol and DLP compared to MS-CT—regardless of the applied scanning protocol. This is in accordance to previous studies reporting effective doses for angiography-mounted FD-CT systems up to twice as high as for MS-CT [ 19 , 23 , 24 ]. In our study, the 14-s scanning protocol of the HS-FD-CT presented with the highest CTDI vol and DLP among the tested scanners and protocols.…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study also showed an improvement in the spatial resolution with CACT compared to MDCT at the same radiation dose. However, recent studies indicate that, for the low range of the X-ray tube high voltage, the related low-and high-contrast image quality of CACT is similar to that of conventional CT [23,24].…”
Section: Discussionmentioning
confidence: 97%
“…We believe that the high accuracy of CTHA-EM in identifying residual tumor demonstrated in the present study is related to several factors. First, the use of CT has many advantages as it provides reliable and reproducible imaging, allows standardized quantitative arterial enhancement assessment via HU quantification, offers easy correlation with the follow-up imaging, and facilitates better image quality with comparable or often lower radiation exposure compared to CBCT [ 24 40 ]. Second, since CTHA-EM uses subtraction imaging, it removes background noise resulting from contrast-media stasis/pooling within the tumor and adjacent vessels and allows reliable HU value normalization.…”
Section: Discussionmentioning
confidence: 99%